2011
DOI: 10.1016/j.jval.2011.02.419
|View full text |Cite
|
Sign up to set email alerts
|

Puk4 Cumulative Exposure to Nonsteroidal Anti-Inflammatory Drugs (Nsaids) and the Progression of Chronic Kidney Disease (Ckd)

Abstract: surement with more than one endpoint is the generation of a cardinal index/score. Without the prioritization and weighting of multiple endpoints a deduction of recommendations might be questionable. METHODS: A pilot study was conducted to elicit patients' preferences about antiviral therapy of chronic hepatitis C. For the Discrete-Choice-Experiment (DCE), 7 attributes were selected with 3 Levels each. Therefore an orthogonal, balanced and efficient design was used and results were analysed with random effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Normal or high dose NSAID prescribing in our study was not significantly associated with eGFR decline within a 2-year time-period. The findings are consistent with large published studies by Yarger et al , 20 Gooch et al , 16 Hemmelgarn et al , 23 Curhan et al , 8 Kurth et al , 19 and Rexrode et al , 21 who found no association between normal dose NSAID use (prescribed or OTC) and renal decline. Equally, a recent systematic review by Nderitu et al , 4 found no significant association between normal dose NSAID use and eGFR decline.…”
Section: Discussionsupporting
confidence: 91%
“…Normal or high dose NSAID prescribing in our study was not significantly associated with eGFR decline within a 2-year time-period. The findings are consistent with large published studies by Yarger et al , 20 Gooch et al , 16 Hemmelgarn et al , 23 Curhan et al , 8 Kurth et al , 19 and Rexrode et al , 21 who found no association between normal dose NSAID use (prescribed or OTC) and renal decline. Equally, a recent systematic review by Nderitu et al , 4 found no significant association between normal dose NSAID use and eGFR decline.…”
Section: Discussionsupporting
confidence: 91%
“…The previous study showed that conventional NSAIDs increased the risk of renal progression and end-stage renal disease in CKD. The large cohort studies from Gooch et al, 6 Hemmelgarn et al, 11 and Yarger et al 12 demonstrated that accelerated CKD progression occurred in 10.9%-13.3% of the study participants. Although high cumulative NSAID exposure was significantly associated with an increased risk of accelerated CKD progression, regular NSAID use was not associated with an increased risk of accelerated CKD progression, especially among Stage 3 CKD patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that regular NSAIDs use does not increase the risk of accelerated CKD progression. 34 36 Nderitu et al 34 proposed that high doses of NSAIDs use results in the increase of the risk which accelerates renal function decline. A possible explanation is that our data were assessed at the baseline and not throughout the study period.…”
Section: Discussionmentioning
confidence: 99%